The role of vitamin C and E in improving hearing loss in patients with type 2 diabetes - Marwan M. Merkhan; Kassim S. Abdullah (Annals of the College of Medicine Mosul, 2020)
Objective: to evaluate the effect of antioxidant vitamins on hearing loss in diabetic patients. Patients and methods: Sixty type 2 diabetic patients with positive pure tone audiogram (PTA) enrolled in the study and divided into two groups: each group consists of thirty patients, group one was put on antioxidant therapy, and group two on placebo therapy, for 2 months duration. Thirty healthy individuals were kept as a control. Fasting blood sugar (FBS), and malondialdehyde (MDA) were measured in all groups. MDA and PTA were repeated after therapy. Results: The FBS and MDA are higher in diabetic patients, and beneficial effects of the administration of vitamin E and C combination on the oxidative stress and significant improvement, with mean differences of 12.5±7.79 decibel (dB), in the sensorineural hearing loss (SNHL) in diabetic patients were obtained. Conclusion: the present study demonstrated that diabetic patients have exaggerated oxidative stress, and administration of vitamin E and C combination had beneficial effect on the oxidative stress, and on the SNHL in diabetic patients with mean differences of 12.5±7.79 dB (p<0.001).